Galactooligosaccharides and Resistant Starch Altered Microbiota and Short-Chain Fatty Acids in an in vitro Fermentation Study Using Gut Contents of Mud Crab (Scylla paramamosain) - Tran, Ngoc Tuan; Tang, Yong; Li, Zhongzhen; Zhang, Ming; Wen, Xiaobo; Ma, Hongyu; Li, Shengkang (Frontiers in Microbiology, 2020)
Dietary carbohydrates are anaerobically fermented by gut microbiota to short-chain fatty acids (SCFAs) conferring gut health benefits. Of all tested prebiotics, galactooligosaccharides (GOS) and resistant starch (RS) were better than any of the others for SCFAs production in mud crab (Scylla paramamosain), a crustacean model. This study further explored the prebiotic potential of GOS and RS in mud crab by assessing their impacts on gut microbiota changes and SCFAs production using in vitro anaerobic fermentation cultures. Both GOS and RS significantly promoted SCFAs production. Bacterial diversity in the GOS group was lower than in RS or control. GOS promoted the growth of Bacteroidetes, while RS promoted Tenericutes. A strong positive correlation was found between the SCFAs production and bacterial abundance; most bacteria per se were correlated with each other. The findings demonstrated the prebiotic potential of GOS and RS in mud crab.